Dynamic google SketchUp software and conventional teaching strategy of students’ conceptual knowledge and procedural knowledge in learning geometry - Tan, Tong Hock; Mohd Ayub, Ahmad Fauzi; Md Yunus, Aida Suraya; Salim, Nur Raidah (Macrothink Institute, 2021)
The purpose of this study is to identify the effect of using dynamic software Google SketchUp (GSU), without software on van Hiele’s theory and conventional teaching strategy of students’ conceptual and procedural knowledge in learning geometry among primary school students. The study was conducted using pre and post-test true experimental methods. This true experimental research involved 96 students from Year Five primary schools in Malaysia. The selection of site or school take into account as convenience and voluntary participation. The study's findings showed significant differences in student's conceptual knowledge and procedural knowledge based on the different types of the strategy group. The post hoc test indicated that using software showed better conceptual and procedural knowledge when compared to without using software on van Hiele’s theory and conventional teaching strategy.